Impact of organizational health-oriented strategies on employees' job performance, perceived medical mistrust as a moderator: A COVID-19 perception-based view - Ye, Mao; Chen, Yu; Liu, Yang; Li, Xiaohuan (Frontiers in Public Health, 2022)
After experiencing the COVID-19 pandemic, employees' health and well-being become a priority for firms. Organizational health-oriented strategies assist them in coping with health-related crises. Based on the social exchange theory, the present study attempts to determine the role of organizational health-oriented strategies in promoting employees' job performance. This study hypothesized that the organizations' health-oriented strategies positively correlate with employees' job performance. This study also assessed the mediating role of employees' psychological wellbeing and trust and moderating role of perceived medical mistrust. For the empirical examination, data of the present study was gathered from the textile sector in China. This study analyzed data through partial least square structural equation modeling (PLS-SEM). For this purpose, Smart-PLS software was used. The outcomes revealed that organizational health-oriented strategies positively enhance the employees' psychological wellbeing, trust, and job performance. Moreover, the results revealed that employees' psychological wellbeing and trust positively mediate the proposed relationships. This study found that perceived medical mistrust moderates the relationship between employees' psychological wellbeing and job performance. However, the findings revealed that perceived medical mistrust does not moderate the relationship between employees' trust and job performance. In addition, the present study's findings provide insights to the firms about the importance of health-oriented strategies. Moreover, this study's findings also serve the literature by providing important theoretical and practical implications.